A resisting enclave of social rights – protecting the children of former workers: C-181/19 Jobcenter Krefeld – Widerspruchsstelle v JD. Issue 5 (October 2021) - Jacqueson, Catherine
The boundaries of financial solidarity between the Member States have long been a hotly debated issue. With Jobcentre Krefeld, the Court puts an end to the saga of the rights of children of former workers and their primary carer. It firmly anchors its ruling in the free movement of workers and distinguishes the case from the Dano and Alimanovic cases.